Formation of competitive advantages of machine-building products - Pererva, O. P. (Teadmus OÜ, Tallinn, 2025)
The report substantiates that achieving high competitiveness of machine-building products requires an integrated approach, which includes the introduction of innovations, increasing production efficiency, compliance with international standards and effective resource management. Only a combination of these factors will allow enterprises of the machine-building industry to ensure sustainable development and take a leading position in the world market.
Keywords: market; competitive advantages; engineering products; competitors; demand; supply